The Impact of Baby Massage on the Growth of Children Aged 0-2 Years - Putri, Noviyati; Sukamto, Ika Sumiyarsi; Nugraheni, Angesti; Argaheni, Niken Bayu; Kusmawati, Iffah Indri (Jurnal Bidan Cerdas, 2025)
Background: Massage has been widely studied because of its potential to promote growth in children. This study aims to evaluate the effectiveness of massage therapy on weight gain in children under 2 years old at the Jenawi Health Center. Methods: A non-randomized controlled trial with a pretest and posttest, involving 70 children under 2 years of age. Participants were divided into an intervention group, which received infant massage therapy for one month, and a control group which did not receive massage. Interventions are given daily by the mother. Data analysis used the Wilcoxon and Mann-Whitney. Results: there was a significant increase in body weight compared to the control group. The mean weight change in the intervention and control group was 485.7 and 350 grams. The Wilcoxon test obtained a z-score of -7,280 (p = 0.001), indicating a statistically significant weight gain from baseline to post-intervention. Additionally, the Mann-Whitney U test revealed a statistically significant difference in weight change between the control and intervention groups (z = -3.269, p = 0.001). Therefore, it can be concluded that massage is effective in increasing the Infant's weight so massage can be used as a routine treatment method to support the weight growth of children under two years old.